Fabrication and analysis of two-wheeler connecting rod for aluminium hybrid composites using finite element method. (30th July 2021) - Parveen, Aasiya; Chauhan, Nathi Ram; Waseem, Mohammad; Suhaib, Mohd
Abstract: In this study, the powder metallurgy process is applied for the development of composite material Al/3 wt% Si3 N4 /4.5 wt% ZrO2 and a 3D model of the connecting rod, as per the engine specifications of TVS Apache 150 motor, is designed using Solidworks software. The model is then imported into ANSYS Workbench for the finite element method to analyse the von-mises stress, elastic strain and deformation on the connecting rod for the particular loading conditions. Moreover, a comparative study is done between the developed connecting rod and the existing Al7068/5 wt% Si3 N4 composite results taken from the literature. From the results, it is revealed that the maximum von-mises stress for Al/3 wt% Si3 N4 / 4.5 wt% ZrO2 composite reduced by 53.54% for big end loading conditions and 71.24% for small end loading conditions. The weight of the connecting rod was found to be 0.2412 kg.